2022
DOI: 10.1001/jamanetworkopen.2022.19678
|View full text |Cite
|
Sign up to set email alerts
|

Association of Molecular Senescence Markers in Late-Life Depression With Clinical Characteristics and Treatment Outcome

Abstract: IMPORTANCE Many older adults with depression do not experience remission with antidepressant treatment, and markers of cellular senescence in late-life depression (LLD) are associated with greater severity of depression, greater executive dysfunction, and higher medical illness burden.Since these clinical characteristics are associated with remission in LLD, molecular and cellular senescence abnormalities could be a possible biological mechanism underlying poor treatment response in this population. OBJECTIVE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
(154 reference statements)
2
8
0
Order By: Relevance
“…https://doi.org/10.1038/s44220-023-00033-z Finally, in a longitudinal study of a subsample of the participants included in the present analysis, we have shown that a higher SASP index at baseline independently predicted a lower remission rate to venlafaxine treatment 29 .…”
Section: Articlesupporting
confidence: 48%
See 2 more Smart Citations
“…https://doi.org/10.1038/s44220-023-00033-z Finally, in a longitudinal study of a subsample of the participants included in the present analysis, we have shown that a higher SASP index at baseline independently predicted a lower remission rate to venlafaxine treatment 29 .…”
Section: Articlesupporting
confidence: 48%
“…On the basis of these SASP markers 27 , our group developed a peripheral SASP index comprising 22 proteins. We validated the SASP index in several studies 28,29 and consistently found a higher SASP index in individuals with LLD compared with healthy individuals 28,30,31 , suggesting that the SASP index might be a marker for accelerated ageing in LLD.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Our previous studies have shown key inflammatory factors part of the SASP are strongly correlated with MDD, medical comorbidities, and severity of cognitive impairment (Diniz et al, 2019;Seitz-Holland et al, 2023). Our previous studies also suggest that higher SASP index scores are correlated with higher rates of non-remission of MDD following treatment (Diniz et al, 2022). MDD has also been associated with telomere attrition and DNA damage (Diniz et al, 2018;Gonçalves et al, 2021;Mendes-Silva et al, 2021;Vieira et al, 2021).…”
Section: Introductionmentioning
confidence: 75%
“…An accelerated aging hypothesis of LLD implies a bidirectional process [ 206 ]. Depressed older adults exhibit an advanced biological age on a multibiomarker index of metabolic and inflammatory measures [ 207 , 208 ] and on structural MRI, where they appear approximately 4 years older than nondepressed individuals [ 198 ]. This accelerated brain aging is further associated with disability and cognitive performance [ 198 ], with depression severity moderating the relationship between brain age and some cognitive measures.…”
Section: Depression and Accelerated Agingmentioning
confidence: 99%